2003
DOI: 10.1136/pmj.79.929.154
|View full text |Cite
|
Sign up to set email alerts
|

Management of irritable bowel syndrome

Abstract: The diagnosis of irritable bowel syndrome (IBS) is made on clinical grounds with appropriate limited investigations to exclude organic disease. IBS is common and may have a significant impact on a patient’s quality of life. Psychological symptoms are common. IBS may benefit from pharmacological and non-pharmacological management. Specific measures should be directed towards the dominant symptoms of constipation or diarrhoea. Several new drugs are currently under evaluation and may prove valuable for subgroups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…15 IBS accounts for up to 50% of consultations with gastroenterologists. 16 Patients with a formal diagnosis of IBS have been reported to have an increased number of consultations per year, both in primary and secondary care, as compared with patients without this diagnosis (8.6-9.0 versus 4.6). 17 Up to 85% of IBS patients undergo an investigation, with the most frequent being an abdominal ultrasound (approximately half) and a colonoscopy (approximately one-third).…”
Section: The Burden Of Ibs On Healthcare Systemsmentioning
confidence: 99%
“…15 IBS accounts for up to 50% of consultations with gastroenterologists. 16 Patients with a formal diagnosis of IBS have been reported to have an increased number of consultations per year, both in primary and secondary care, as compared with patients without this diagnosis (8.6-9.0 versus 4.6). 17 Up to 85% of IBS patients undergo an investigation, with the most frequent being an abdominal ultrasound (approximately half) and a colonoscopy (approximately one-third).…”
Section: The Burden Of Ibs On Healthcare Systemsmentioning
confidence: 99%
“…Les croyances mystiques seraient plus fré-quemment exprimées par le patient souffrant de SII comparé au patient souffrant de CC en Côte-d'Ivoire. Ce constat permettrait, s'il était confirmé par d'autres études, de distinguer dans une approche pragmatique basée sur les symptômes, le patient souffrant de SII, lorsque celui-ci exprimerait des croyances mystiques pendant la consultation, de celui souffrant uniquement de CC et d'en tenir compte dans sa prise en charge [25,26].…”
Section: Resultsunclassified
“…In the UK,~17% of the general population live with IBS, and up to 50% of all general practitioner (GP) visits for gastrointestinal disturbances relate to IBS symptoms [19]. IBS poses a significant personal, societal and economic burden [20][21][22], thus clinically effective and pragmatic treatment options which serve to reduce the symptoms of IBS are much needed. Although several reviews have previously concluded that probiotics improve IBS symptoms including abdominal pain [23][24][25][26][27][28], many reviews feature studies investigating the use of composite probiotic mixtures containing several strains of Lactobacillus, Bifidobacterium and Propionibacterium, which hampers the assessment of specific strains in relieving IBS symptoms.…”
Section: Discussionmentioning
confidence: 99%